The analysis of the result differences in the time segments of a handball match for young female handball players - Vuleta, D.; Ohnjec, K.; Kanjugovic, I. (Acta Kinesiologica, 2013)
The aim of the research has been to establish the differences between the results performed in particular time segments of a handball match (10 minute quarters) by comparing the winning and the losing teams at the 2012 National Championship for young female handball players (under 16). Situational parameters, defined as a partial result increase in particular periods of matches, and the result differences, recorded at the end of each quarter, have been included in the analysis, all being gathered at the final games of the Croatian Championship for young female handball players (under 16) in the 2011/2012 season. Analysis of variance and Mann-Whitney U-test have been applied to determine the differences, and the results of both showed that the winning and the losing team differ in all four observed segments of the handball match, in respect to the partial result increase, as well as regarding the result differences at the end of each quarter.